2020
DOI: 10.1016/j.clnu.2019.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Milk analysis using milk analyzers in a standardized setting (MAMAS) study: A multicentre quality initiative

Abstract: Background: Human milk analyzers are increasingly used to rapidly measure the macronutrient content in breast milk for individual target fortification, to reduce the risk of postnatal growth restriction. However, many milk analyzers are used without calibration, validation or quality assurance. Aims: To investigate measurement quality between different human milk analyzers, to test whether accuracy and precision of devices can be improved by establishing individual calibration curves, and to assess long-term s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…We measured the macronutrients (carbohydrate, protein and lipids) and total energy with the spectrophotometry technique, through INFRARED ANALYSIS using Miris Human Milk Analyzer™ (Miris AB, Uppsala, Sweden) (already validated for human milk analysis) following good clinical laboratory practice [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…We measured the macronutrients (carbohydrate, protein and lipids) and total energy with the spectrophotometry technique, through INFRARED ANALYSIS using Miris Human Milk Analyzer™ (Miris AB, Uppsala, Sweden) (already validated for human milk analysis) following good clinical laboratory practice [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The most common analytical method used for measuring macronutrients in the studies reviewed was infrared analysis. A growing body of evidence suggests that infrared analysis can reliably measure total nitrogen (e.g., crude protein) and fat in human milk, with appropriate sample handling and instrument calibration, though measurements of lactose were less accurate, and the measurement of total carbohydrates in human milk has not been validated (36)(37)(38)(39)(40)(41)(42) . None of the reviewed studies used reference methods suggested by the USDA (8) to measure total protein or total fat, and only 1 study used reference methods for measuring lactose, which limits the ability to draw conclusions about actual nutrient ranges.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed each sample of unfortified milk once. Performance testing of our analyzer in collaboration with the MAMAS study [24] revealed high accuracy (r = 0.99 true protein vs. elemental analysis, r = 0.98 fat vs. Mojonnier [25] and reliability (coefficient of variation 5.2% protein, 1.6% fat; email communication with Ms. Celia Kwan, February 2017). From 37 participating infants, we included nutrient data from 1626 milk samples.…”
Section: Milk Collection and Analysismentioning
confidence: 99%